2020
DOI: 10.1111/josh.12894
|View full text |Cite
|
Sign up to set email alerts
|

Investing in Public School Kitchens and Equipment as a Pathway to Healthy Eating and Equitable Access to Healthy Food

Abstract: BACKGROUND:We gathered baseline data about student need of healthy, free school food, and if current school meal programming serves students in need of healthy free school food, in anticipation of the completion of a district-wide kitchen infrastructure and educational farm project in a high-poverty urban school district. METHODS:We used mixed methods to assess student hunger, whether the school meal program met student needs, and to determine associations between presence of a cooking kitchen and perceptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…School districts can work toward these improvements by applying the following: Stakeholders and decision‐makers should communicate about the benefits, with a focus on health, when rolling out a new breakfast program. Those involved in the implementation of BIC should also be informed that the breakfast items meet government nutrition standards. Teachers who are satisfied with the program and have established a successful daily BIC routine can provide “best practice” training sessions for other teachers. Ensuring that each student has access to fresh fruit may improve teacher approval. Parents and staff were more likely to perceive unpackaged, fresh lunches made in cooking kitchens as healthy compared to packaged and reheated lunches 36 . Thus, investing in kitchen equipment that allows the food service staff to cook more meals may improve the teachers' perceptions toward the breakfast items' healthfulness and variety. Policy and funding focused on school food service programs and infrastructure could provide the resources that would allow school meals to shift from frozen and packaged to freshly cooked. …”
Section: Implications For School Health and Equitymentioning
confidence: 99%
“…School districts can work toward these improvements by applying the following: Stakeholders and decision‐makers should communicate about the benefits, with a focus on health, when rolling out a new breakfast program. Those involved in the implementation of BIC should also be informed that the breakfast items meet government nutrition standards. Teachers who are satisfied with the program and have established a successful daily BIC routine can provide “best practice” training sessions for other teachers. Ensuring that each student has access to fresh fruit may improve teacher approval. Parents and staff were more likely to perceive unpackaged, fresh lunches made in cooking kitchens as healthy compared to packaged and reheated lunches 36 . Thus, investing in kitchen equipment that allows the food service staff to cook more meals may improve the teachers' perceptions toward the breakfast items' healthfulness and variety. Policy and funding focused on school food service programs and infrastructure could provide the resources that would allow school meals to shift from frozen and packaged to freshly cooked. …”
Section: Implications For School Health and Equitymentioning
confidence: 99%
“…A wider study would be needed to prove generalisability of the findings. However, research in the field lends support to the case study findings (National Nutrition Council of Finland 2017; Morgan and Sonnino 2007;Persson Osowski, Göranzon, and Fjellström 2012;O'Neill et al 2020;Irish Heart Foundation 2015).…”
Section: Methodsmentioning
confidence: 73%
“…Serving school meals in packaging may deter students from eating it due to the texture of the meal but also due to other children's perceptions of the meal (O'Neill et al 2020). The same study concluded that scratch-cooked meals had less stigma and were better perceived by both students and their parents which lead to increased consumption.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is rarely fresh but often packaged reheated food with a bad presentation. However, food preparation and presentation appears to influence student consumption of school food and adult perception of school meal quality [25]. Given that emergency HCWs work under the time pressure of urgent care, they must both take care of patients and themselves i.e., finding the time to eat and drink.…”
Section: Introductionmentioning
confidence: 99%